Pediatric asthma in developing countries: challenges and future directions. Issue 2 (15th April 2022) - Trikamjee, Thulja; Comberiati, Pasquale; Peter, Jonny
Abstract : Purpose of review: Asthma continues to be a significant health problem worldwide, and epidemiological studies in the last few decades have consistently shown a marked increase in childhood asthma prevalence. The International Study of Asthma and Allergies in Childhood (ISAAC) showed significant geographic variability in prevalence, and larger associations with morbidity and mortality in low-middle income countries (LMICs). The Global Burden of Disease estimated that 420, 000 deaths occurred globally from asthma in 2016, and although asthma prevalence is higher in high-income countries, most asthma-related mortality occurs in LMICs. The general health of a population is measured, in part, by the under-5 childhood death rate, and developing countries still account for more than 80 percentage of child deaths in the world, highlighting the need for efforts to reduce disease burden in these regions. Recent findings: The burden of asthma is higher in developing countries and underserved populations. Despite this, LMICs still face many barriers to appropriate allergy and asthma care, resulting in significant morbidity, potentially preventable asthma deaths, and economic consequences. A 2017 survey of 112 countries participating in the Global Asthma Network found that only 26 countries (23%) had a national asthma plan for children, with a lower proportion in LMICs. Summary: The rising asthma prevalence and high asthma-related death rates in LMICs suggest that global efforts in improving asthma diagnosis and care are not reaching the most vulnerable communities. Lack of appropriate diagnosis, availability of viable treatment options, and access to specialised care still remain a challenge in many parts of the world. Though barriers to achieving better outcomes differ in specific populations, many LMICs share similar barriers relating to accessibility.